Scarring impairment by polyhydroxybutyrate-co-hydroxyvalerate bilayer structures-laden adipose stem cells - Zonari, A. A. C. (2014)
The limited outcomes of commercially available skin substitutes reinforce the fact that the regeneration of functional skin remains elusive. Recently, our group developed a bilayer structure based on poly(3-hydroxybutyrate-co-hydroxyvalerate) (PHBV) with properties that favor skin cells performance thus representing a promising strategy to improve wound healing3. Therefore, this work aimed to further advance this knowledge by assessing the regenerative potential of the PHBV-laden adipose stem cells in a full-thickness rat wound model. Adipose stem cells (ASCs) were isolated from GFP transgenic rats (Lewis F455.5/Rrrc) were seeded (1x106 cells) on PHBV bilayer structures prepared as previously described. Constructs were transplanted to rat full-thickness wounds according to the following groups (n=4): empty wound (control), scaffold (PHBV) and scaffold plus cells (PHBV+ASCs). Tissue explants were retrieved on days 7, 14, 21 and 28 post-surgery. Wound closure was followed along the implantation time and correlated with histological (localization of GFP-ASCs, matrix deposition/organization, neovascularization) and molecular analysis (GFP, VEGF, bFGF, TGF-β1 and α-SMA). Statistical analyses were performed using ANOVA with Bonferroni post-tests. A significant different (p<0.05) percentage of wound closure was only observed between control and PHBV groups at day 14. At the endpoint of the experiment all the wounds were closed and the PHBV structure was completely degraded. GFP-positive ASCs were onlydetected at the wound area up to 7days. An up-regulation of VEGF and bFGF was also detected at this time-point, consequently leading to a significant higher vessel density in the PHBV+ASC group. Additionally, in the presence of the PHBV structure a down-regulation of TGF-β1 and α-SMA was detected. The PHBV structure allowed ASCs to provide the necessary factors for enhanced vascularization and acted as template for guiding the wound healing process impairing myofibroblasts differentiation and consequently scarring. Therefore, we can conclude that PHBV-laden ASCs represent a promising approach for skin regeneration.